Seasonal changes in blood oxygen transport and acid-base status in the tegu lizard, Tupinambis merianae - Andrade, D. V.; Brito, S. P.; Toledo, L. F.; Abe, Augusto Shinya [UNESP] (Elsevier B.V., 2004)
Oxygen-binding properties, blood gases, and acid-base parameters were studied in tegu lizards, Tupinambis merianae, at different seasons and temperatures. Independent of temperature and pH, blood oxygen affinity was higher in dormant lizards than in those active during the summer. Haematocrit (Hct) and hemoglobin content ([Hb]) were greater in active lizards resulting in a higher oxygen-carrying capacity. Nucleoside triphosphate content ([NTP]) was reduced during dormancy, but the ratio between [NTP] and [Hb] remained unchanged. Dormancy was accompanied by an increase in plasma bicarbonate ([HCO(3)(-)]PI) and an elevation of arterial CO(2) partial pressure (P(aCO2)) and CO(2) content in the plasma (C(PlCO2)). These changes in acid-base parameters persist over a broad range of body temperatures. In vivo, arterial O(2) partial pressure (Pa(O2)) and O(2) content (Ca(O2)) were not affected by season and tended to increase with temperature. Arterial pH (pH(a)) of dormant animals is reduced compared to active lizards at body temperatures below 15 degreesC, while no significant difference was noticed at higher temperatures. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: acid-base balance; reptiles; adaptation; seasonal; blood; oxygen transport; temperature; Bohr effects; metabolism; depression; teiidae (Tupinambis merianae)